Coagulation Failure in Patients With Acute‐on‐Chronic Liver Failure and Decompensated Cirrhosis: Beyond the International Normalized Ratio. Issue 6 (9th November 2018) - Blasi, Annabel; Calvo, Andrea; Prado, Verónica; Reverter, Enric; Reverter, Juan Carlos; Hernández‐Tejero, María; Aziz, Fátima; Amoros, Alex; Cardenas, Andres; Fernández, Javier
Abstract : Balanced hemostasis with hypocoagulable and hypercoagulable features may occur in acute‐on‐chronic liver failure (ACLF). The characteristics and prognostic impact of the coagulation profile in ACLF are unknown. Consecutive patients with ACLF (n = 36) and acute decompensation (AD; n = 24) were included. Blood samples for thromboelastometry (TE) were obtained at admission and 72 hours thereafter. The coagulation profile was evaluated in patients with and without ACLF and in those with and without systemic inflammatory response syndrome. The impact of the coagulation profile on transfusion requirements, bleeding events, and short‐term survival was assessed. At admission, patients with ACLF showed more hypocoagulable characteristics compared to AD subjects, with prolonged time to initial fibrin formation and clot formation time and decreased maximum clot firmness and alpha‐angle values. TE parameters worsened at 72 hours in ACLF but improved in patients with AD. Prevalence of a hypocoagulable profile (three or more TE parameters outside range) was significantly higher in patients with ACLF either at admission (61% versus 29% in AD; P = 0.03) or during follow‐up. Hypocoagulability correlated with systemic inflammation and was associated with higher 28‐day (45% versus 16%; P = 0.02) and 90‐day (52% versus 19%; P = 0.01) mortality rates but not with transfusion requirements or bleeding. Prolonged time to initial fibrin formation (extrinsic TE assay >80 seconds) and Model for End‐Stage Liver Disease score at baseline were independent predictors of 28‐day mortality. Conclusion: Patients with ACLF frequently show hypocoagulable features with prolonged time to initial fibrin formation and clot formation time and reduced clot firmness; these alterations worsen after admission, correlate with systemic inflammation, and translate into higher short‐term mortality; hypofibrinolysis could contribute to organ failure in ACLF.